Highly-sensitive chimerism analysis in blood after allogeneic hematopoietic cell transplantation in childhood leukemia: Results from the Nordic Microchimerism Study - Haugaard, Anna Karen; Madsen, Hans Ole; Masmas, Tania Nicole; Vettenranta, Kim; Buechner, Jochen; Mellgren, Karin; Turkiewicz, Dominik; Rosthøj, Susanne; Marquart, Hanne Vibeke; Heilmann, Carsten; Müller, Klaus Gottlob; Ifversen, Marianne (Frontiers in Hematology, 2023)
Analysis of chimerism in blood post‐HCT using STR‐PCR is routinely applied in parallel with quantification of MRD to predict relapse of leukemia. Real time quantitative PCR (RQ-PCR) chimerism is 10‐ to 100‐fold more sensitive, but clinical studies in children are sparse. In a prospective multicenter study, we analyzed increasing mixed chimerism (IMC) in blood samples following transplantation for leukemia in 64 children. IMC was defined as a minimum increase of either 0.1% or 0.05% recipient DNA between two samples or a ≥10-fold increase. Samples closer than 30 days to diagnosis of relapse were omitted. The risk of relapse was higher in children with IMC of both 0.1% and 0.05% compared to children without IMC (27.8 (95% CI 4.4-175.8; P< .001), and 18.4 (95% CI 2.8-120.5; P=0.002), respectively). From the date of IMC, the 3-year CI of relapse or MRD-positivity was 26.7% (CI 9.4-47.0) and 18.5% (6.4-35.3) for IMC ≥ 0.1% (n=27) and ≥ 0.05% (n= 40), respectively. In the subset of children without an IMC ≥ 0.1% or ≥ 0.05%, CI of relapse or molecular relapse were 16.7% (5.0 -34.1) and 10.8% (3.4 -23.3), respectively. In all cases with a relapse undetectable by IMC, MRD remained undetectable prior to relapse and standard chimerism negative. In a landmark analysis, neither an IMC ≥ 0.1% nor ≥ 0.05% prior to 90 days post‐HCT was significantly associated with an increased relapse incidence. These results indicate that the serial monitoring of RQ‐PCR chimerism in peripheral blood post-HCT may be a valuable supplement to the minimal residual disease analysis for an early detection of relapse in acute childhood leukemia.